The homoaffective stable union according to the Supreme Court and the Constitution of the Republic of 1988 (Research, Society and Development, 2022)
As harmful as the interference of the State in the field of private life and intimacy is the omission of the Public Power in areas in which timely and effective action is an indispensable condition for the maintenance of the dignity of the human person and other fundamental guarantees, stamped in the Constitution of the Republic, particularly in the spheres in which the state entity is required an obligation to do so. In this article, founded on a bibliographic review, an emblematic case of inertia of the Legislative Power of the Union was presented, by expressly including in art. 1,723 of the Civil Code, and, in part, in Art. 226, § 3, of the CF/88, the limitation of stable union, as a family entity, only in relation to man and woman. In light of this, once regularly provoked, the Supreme Federal Court (STF), through ADIn No. 4,277/DF, applied interpretation according to the Constitution to the aforementioned provisions, in order to also include, in the legal dimension of the married status, the stable union between people of the same sex (homosexuals). To this end, the Court, represented in this article by excerpts from the vote drawn up by the then Minister of the Supreme Court, Celso de Mello, notably from affirming the primacy of the Constitution and fundamental rights and principles, as well as reflections on the function of judicial activism in the exercise of the counter-majority function, in view of the prolonged omission of the public power in relation to groups composed of social minorities.